Pengaruh Pemberian N, P dan K Terhadap Pertumbuhan Tanaman Jati (Tectona grandis L.f) Klon PHT I dan PHT II Sampai Umur Satu Tahun (Studi Kasus di KPH Kendal dan Randublatung, Jawa Tengah) - , IMAM SUHUDI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
, t he decline was Soil fertility on the forest land is now decreasing caused by either natural factors, human activities or the interaction between them such as harvesting, erosion, forest fires and intensive silviculture that neglected conservation rules. Restoring soil fertility can be achived by fertilization. The addition of N fertilizer at the early growth of teak only contributed on vegetative growth, with the addition of complete fertilizer, we expected to gain optimal vegetative growth and preserved plant health. research was carried out using The Split-Split Plot consisted of 27 treatments. Parameter for measurement diameter, height, content of N in urea, content of P in TSP fertilizers, content of K in KCl fertilizer, chlorophyll content in leaf, N, P and K content in soil, soil pH, N, P and K content in leaf. M Soil analysis results obtained K content decreased, whereas N and P slightly increased. The higher rate of plant growth, the addition of N and P content of the less. easurements results of N, P and K content in leaves shown that the N and P content were decreased, while the K content tended to increase compared to plant before fertilizing. The average of clorofil content increased 11,25 ccu (chlorofil content unit) compared before fertilizing. Further test the relationship with the content of N fertilization treatment, P, K in the soil, N, PK on the leaves and chlorophyll content did not influence the real difference. The best height growth obtained by N 50 g and P 50 g, the best diameter growth obtained by N 50 g and K 25 g. Addition of N, P and K at the highest dose still produced a linear growth curve, so that the best dosage for optimal growth of plant has not been found. The best fertilizer combinations for height and diameter growth of teak plants up to 1 year is N2P2K1 (50 g urea, TSP 50 g and 25 g KCl).